Hypotyposis of the virtues of the Valido: heraldry and communication of a political anomaly in early modernity: the Duke of Lerma - Guillén Berrendero, José Antonio (Eikón / Imago, 2025)
The text proposes an interpretation of the Duke of Lerma’s shrewd use of heraldry. As Philip III’s favourite, Lerma launched an ambitious self-promotional campaign shaping his own image in what may be aptly described as self-fashioning avant la lettre. We shall analyse Lerma’s heraldic displays from his early years as Duke of Gandía up to his rise to power. The status of royal favourite was nonstandard in early modern polities. Yet Lerma made it part of the visual culture shared by Europe’s nobility at the time. His coat of arms was transformed into a hypotyposis of his own heroic virtues and those of the Sandoval lineage.